Coda wave attenuation in Mara Rosa seismic zone - schmidt, kellin (2013)
Small local earthquakes from aftershock sequence in Mara Rosa, Goiás state, Brazil were used to estimate the coda wave attenuation in the frequency band of 1 to 20 Hz. The time-domain coda-decay method of a single backscattering model is employed to estimate frequency dependence of quality factor (Qc) of coda waves modeled using Qc = Q0fη, Q0 is the coda quality factor at a frequency of 1 Hz and η is the frequency parameter. Qc values have been computed at central frequencies and (band) of 1.5 (1-2), 3.0 (2-4), 6.0 (4-8), 9.0 (6-12), 12 (8-16) and 18 (12-24) Hz in the lapse time ranging from 5 to 25 sec in step of 5 seconds. It was determined the functional form Qc = (10.78) f(1.84)) .